DEVELOPMENT AND CHARACTERIZATION OF FENOFIBRATE TABLET BY COMAPARING TWO DIFFERENT SOLUBILITY AND DISSOLUTION ENHANCEMENT METHODS - Dua, J S; Kaur, Beerpal; Prasad, D N (Asian Journal of Pharmaceutical Research and Development, 2018)
Fenofibrate is a drug included in BCS class II category, generally used to reduce cholesterol level in patient having a risk of cardiovascular disease. The main aim of this research was to ameliorate solubility and dissolution profile of Fenofibrate with comparison between two different methods i.e. Solid dispersion and liquisolid technique. In liquisolid system, a dry freely flowing and compressible powder mixture was obtained which absorb drug solution or suspension in non-volatile solvent. While in case of solid dispersion drug was dispersed with suitable hydrophillic carrier with or without volatile solvent to get powder material. Two formulation of Fenofibrate solid dispersion were prepared by solvent evaporation method using β-CD as a hydrophillic carrier with ratios 1:1 and 1:3. In case of liquisolid technique, two liquisolid compacts were prepared with ‘R’ value 20:1 and 40:1 using Avicel PH 102 as a carrier and Aerosil 200 as a coating material. All the formulations were characterized by FTIR, DSC and solubility studies. Precompression studies of all the batches were done by determining angle of repose (25.100- 35.020), bulk density (0.51- 0.56 g/ml), tapped density (0.60-0.66 g/ml), carr’s index (15.61-19.03%) and hausner’s ratio (1.13-1.25). Post compression evaluation was done by checking hardness (4-5 kg/cm2), thickness (3.56-4.01mm), friability (0.54-0.75%), disintegration time (3.50-5.56min), drug content (80.34-95.05%) and in-vitro drug release (81.55-92.93%). Out of all the four batches SD2 batch that was prepared by solid technology showed an excellent result by releasing drug at 96.91 %. Key words- Fenofibrate, Solid dispersion, Liquisolid compact, Avicel PH 102, Aerosil 200.